Hospitality security managing security in today's hotel, lodging, entertainment and tourism environment - Clifton, Darrell (Boca Raton, FL CRC Press, 2023)
"Hospitality Security: Managing Security in Today's Hotel, Nightlife, Entertainment, and Tourism Environment, Second Edition provides experience-based, proven methods for preventing and resolving the challenges faced by today's hospitality security staff and leadership. This new edition includes expanded content on premises liability, security force behavioral recognition, workplace violence, active shooter scenarios, evacuation planning, social media and guest reviews, and hotel scams. Additional coverage on nightclubs and bars has been added as well as four entirely new chapters on specialized security for events and venues, crime prevention through environmental design, advances in technology, and industry trends for the gaming and hospitality sector. Ideal for novices and veterans alike, Hospitality Security, Second Edition is an accessible, reader-friendly reference that enables security directors to evaluate what risks are inherent to hospitality environments, to analyze those risks through threat and vulnerability assessments, and to develop methods to mitigate or eliminate them-all the while keeping customers and personnel safe and improving the bottom line"--
Includes index.
Keywords: Hospitality industry -- Management; Hotels -- Security measures; Restaurants -- Security measures